Designing Suburban Futures New Models from Build a Better Burb - Williamson, June. (Island Press/Center for Resource Economics : Imprint: Island Press, 2013)
Suburbs deserve a better, more resilient future. June Williamson shows that suburbs aren't destined to remain filled with strip malls and excess parking lots; they can be reinvigorated through inventive design. Drawing on award-winning design ideas for revitalizing Long Island, she offers valuable models not only for U.S. suburbs, but also those emerging elsewhere with global urbanization. Williamson argues that suburbia has historically been a site of great experimentation and is currently primed for exciting changes. Today, dead malls, aging office parks, and blighted apartment complexes are being retrofitted into walkable, sustainable communities. Williamson shows how to expand this trend, highlighting promising design strategies and tactics. She provides a broad vision of suburban reform based on the best schemes submitted in Long Island's highly successful "Build a Better Burb" competition. Many of the design ideas and plans operate at a regional scale, tackling systems such as transit, aquifer protection, and power generation. While some seek to fundamentally transform development patterns, others work with existing infrastructure to create mixed-use, shared networks. Designing Suburban Futures offers concrete but visionary strategies to take the sprawl out of suburbia, creating a vibrant, new suburban form. It will be especially useful for urban designers, architects, landscape architects, land use planners, local policymakers and NGOs, citizen activists, students of urban design, planning, architecture, and landscape architecture.